A Robust Framework for Epidemic Analysis, Prediction and Detection of COVID-19 - Hassan, Farman; Albahli, Saleh; Javed, Ali; Irtaza, Aun (Frontiers in Public Health, 2022)
COVID-19 has become a pandemic, with cases throughout the world, and especially widespread disruption in some countries, such as Italy, US, India, South Korea, and Japan. Early and reliable detection of COVID is mandatory to control the spread of infection. Moreover, prediction of COVID spread in near future is also crucial to better plan for the disease control. For this purpose, we proposed a robust framework for the analysis, prediction, and detection of Covid-19. We make reliable estimates on key epidemic parameters and make predictions on the point of inflection and possible washout time for various countries around the world. The estimates, analysis and predictions are based on the data gathered from Johns Hopkins Center during the time span of April 21 to June 27, 2020. We use the normal distribution for simple and quick predictions of the coronavirus epidemic model and estimate the parameters of Gaussian curves using the least square parameter curve fitting for several countries in different continents. The predictions rely on the possible outcomes of Gaussian time evolution with the central limit theorem of statistics the predictions to be well justified. The parameters of Gaussian distribution, i.e., maximum time and width, are determined through a statistical χ2 -fit for the purpose of doubling times after April 21, 2020. For Covid-19 detection, we proposed a novel method based on the Histogram of Oriented Gradients (HOG) and CNN in multi-class classification scenario i.e., Normal, COVID-19, viral pneumonia etc. Experimental results show the effectiveness of our framework for reliable prediction and detection of COVID-19.